Exergy-loss analysis of a typical geothermal power plant system in the Philippines - Cabigon, Noel Papas (Animo Repository, 1995)
Energy-loss minimization is now considered the modern effective resource utilization evaluation technique. This method has been applied to almost all forms of resources. Currently, it is extensively applied in energy resource utilization and in process and equipment design. This work deals with exergy-loss analysis on a typical geothermal power plant system in the Philippines. The goal of the study is to determine the benefits of exergy-loss evaluation to effectively optimize the design of a geothermal power plant system in the Philippines. This is done by identifying design parameters that grossly affect or significantly influence the efficiency of a geothermal power plant system. Results show that wellbore design parameters such as diameter, pipe smoothness and total depth significantly influence exergy-loss on production wells. Likewise, the diameter, smoothness, length and pipeline accessories (e.g., valves, etc.) of cross-country and downcomer pipelines and thickness of insulation grossly affect exergy-loss in the steam gathering system. The parameter that influence exergy-loss in the power plant, however, is the fluid exit temperature. All these parameters are within the control of designers and investors the proper evaluation of these parameters leads to minimum exergy losses and virtually improve over-all efficiency. Other parameters that also significantly affect exergy losses: fluid and dead state properties, are beyond the designers' control.